2015
DOI: 10.1103/physrevb.92.085403
|View full text |Cite
|
Sign up to set email alerts
|

Supercurrent reversal in Josephson junctions based on bilayer graphene flakes

Abstract: We investigate the Josephson effect in a bilayer graphene flake contacted by two monolayer sheet deposited by superconducting electrodes. It is found that when the electrodes are attached to the different layers of the bilayer, the Josephson current is in a π state when the bilayer region is undoped and in the absence of vertical bias. Applying doping or bias to the junction reveals π − 0 transitions which can be controlled by varying the temperature and the junction length. The supercurrent reversal here is v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The appearance of these structures fueled theoretical and experimental investigations on the behavior of massless and massive particles in such junctions. For example, few works have investigated different domain walls that separate, for instance, different type of stacking [19][20][21] or even different number of layers [22][23][24] . These theoretical investigations showed that the transmission probabilities through SL/BL interfaces exhibits a valley-dependent asymmetry which could be used for valley-based electronic applications [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…The appearance of these structures fueled theoretical and experimental investigations on the behavior of massless and massive particles in such junctions. For example, few works have investigated different domain walls that separate, for instance, different type of stacking [19][20][21] or even different number of layers [22][23][24] . These theoretical investigations showed that the transmission probabilities through SL/BL interfaces exhibits a valley-dependent asymmetry which could be used for valley-based electronic applications [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the interface between the superconducting (S) and graphene (G) regions was found to be significantly more transparent than in previous experiments 9, [15][16][17][18][19][20][21][22][23][24][25][26][27] . These experimental advances may allow to verify some of the theoretical predictions for graphene-superconductor heterostructures, such as anharmonic phase-current relation of supercurrent at low temperatures in superconductor-graphenesuperconductor (SGS) junctions in monolayer [28][29][30][31] and bilayer 31,32 graphene, supercurrent quantization in quantum point contacts 33,34 , specular Andreev reflection [35][36][37][38] , detection of valley polarization 39 , interplay of strain and superconductivity [40][41][42] etc. in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…in the near future. The theoretical work has mainly focused on short SGS junctions to date [32][33][34]41,43,44 , where the length of the normal region L is smaller than the superconducting coherence length ξ 0 = vF ∆0 . In addition, it was usually assumed that the width W of the junction is much larger than L. Although the long junction regime has been studied theoretically for superconductor-normal metalsuperconductor (SNS) systems [45][46][47][48][49][50][51] , the physics of long SGS junctions is less explored.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the structural characteristic of a graphene heterostructure, e.g. a step-like bilayer/monolayer graphene interface, compared to covalent bonds, van der Waals interactions can lead to special properties which are considerably different from those of pristine monolayer and even bilayer graphene sheets in some cases [2,3,4,5].…”
Section: Introductionmentioning
confidence: 99%